SPASIAL STATISTIK UNTUK ESTIMASI DAN PERAMALAN PRODUKSI PERTANIAN STUDI KASUS: KABUPATEN INDRAMAYU DAN SUBANG - Mubekti Mubekti (Jurnal Teknologi Lingkungan, 2008)
Applied Study on Agricultural Production estimate and Forecast by using Area Frame Sampling in Indramayu and Subang Districts is based on the successfulness of ‘Area Frame Design’ development for the whole Java Island. A brief explanation of design ispresented to refresh its basic idea. The methodology of the study is discussed and the mathematical formulation to estimate rice refers to direct expansion approach is presented. The main aim of the study is to prove that area frame sampling is reliableto implement for rice production estimate and forecast. For that purpose, sample segments were extracted and inside the segment crop cutting was conducted. Three times ground survey were conducted to map rice growing stage and crop cutting. Theanalysis of ground data for both yield and harvest area was done then production estimate was derived. Furthermore, harvest area forcast for next three months after survey-1 was also conducted. Regarding to the man power capability and the results in both districts, it is considered that area frame sampling is feasible to implement indistrict level.